Perspektif Mahasiswa Prodi Pendidikan Kimia tentang Integrasi: Konseptual Ilmu Sosial dalam Pengetahuan Islam, Paradigma Integrasi-Interkonektif: Epistemologi Bayani, Burhani dan Irfani, Perspektif Mahasiswa: Integrasi-Interkonektif - Binti Astuti; Eva Latipah; Muqowim, Muqowim (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Integration is an attempt to unite Islamic knowledge and general knowledge. This integration with Amin Abdullah's view will likely result in difficulties in balancing Islamic and general studies, which are often not very successful due to the desire of both sides to successfully build a closely related system. The purpose of the research is to know the perspective of students of chemistry education on the integration of social sciences and humanities. This research uses descriptive qualitative methods, the method used in qualitational research is data collection through observations and interviews, and documentation. The results of this research show that the perspective of students of chemistry education, students of State Islamic University Sunan Kalijaga through integration with responsibility, answers to the curriculum of the campus, so that students not only learn about religious sciences but also general sciences. Humanism and social sciences are general sciences that are integrated with religious sciences. Each student has a unique perspective related to the knowledge of social sciences and humanities.